Activation of telomerase via madecassic acid enhances the developmental competence of the SCNT-derived bovine embryos - Zaheer Haider; Safeer Ullah; Tahir Muhammad; Chalani Dilshani Perera; Muhammad Tayyab Khan; Asif Jan; Seung-Eun Lee; Seo-Hyun Lee; Sung Woo Kim; Muhammad Idrees; Muhammad Idrees; Il-Keun Kong; et al. (Frontiers in Cell and Developmental Biology, 2025)
Somatic cell nuclear transfer (SCNT) is important in assisted reproductive technologies. However, its reprogramming efficiency remains low. A considerable drawback of SCNT-cloned embryos is the reduction in telomerase activity, which is crucial for DNA stability and genetic and epigenetic reprogramming. The present study aimed to examine the effects of madecassic acid (MA), a potent telomerase activator, on the developmental rate, embryonic genome activation, and implantation potential of SCNT-derived bovine embryos. The treatment of bovine signal cell-cloned zygotes with 3.0 μg/mL MA significantly increased embryo cleavage (71.5%) and blastocyst rate (28.1%) compared with that in non-treated (control) SCNT-cloned bovine embryos. In addition, MA treatment enhanced the bovine granulosa cells' telomerase activity and telomerase expression are assessed using qTRAP assay and ELISA. Of note, MA enhanced the expression of embryonic genome activation (EGA)-related genes including NFYA, SP1, DPRX, GSC, CTNNB1, DUX, and ARGFX in MA-treated cloned embryos compared to the control group. Moreover, MA-treatment of cloned embryos showed substantially less DNA damage than the control SCNT embryos. Mechanistically, MA activation of telomerase reverse transcriptase (TERT) significantly enhanced the nuclear localization of β-catenin and c-Myc and improved EGA. Reduction in the nuclear localization of this triose may be the leading cause of reduced EGA in cloned embryos. In conclusion, MA impacted the EGA reprogramming and development of cloned bovine embryos via probable activation of TERT. This telomerase activator may have the application of improving SCNT-cloned bovine embryos.